Effect of ozone technology applications on physical characteristics of red cayenne pepper (Capsicum frutescens L.) preservation. (May 2019) - Sasmita, E; Restiwijaya, M; Yulianto, E; Yuliani,; Arianto, F; Kinandana, A W; Nur, M
Abstract: Research on the application of ozone technology to red cayenne pepper had been done. The purpose of this research was to determine the changes in the physical characteristic, i.e. TPA (Texture Profile Analysis) and color parameters ( L, a *, b *) of red cayenne pepper by treated with ozone technology. The research method was red cayenne pepper were not sprayed with ozonated water then stored in room temperature, air-conditioner room temperature, cold storage, cold storage dedicated ozone (R0, A0, C0, and Z0) and red cayenne pepper were sprayed with ozonated water then stored in room temperature, air-conditioner room temperature, cold storage, cold storage dedicated ozone (R1, A1, C1, and Z1). The storage times were five days, ten days, 15 days, 20 days, 25 days, and 30 days. During the storage period, the visual appearance, change in texture, color, and weight loss were measured. The results showed that ozone technology treatment and the length of storage time influenced the texture, color, and weight loss of red cayenne pepper as a conclusion the red cayenne pepper treated by sprayed with ozonated water and stored in cold storage dedicated ozone could maintain the quality of red cayenne pepper for 30 days.